Recognition of pigment layers in illuminated manuscripts by means of Kalpha/Kbeta and Lalpha/Lbeta ratios of characteristic X-rays - Trojek, Tomás; Cechák, Tomás; Musílek, Ladislav (Applied radiation and isotopes, 2010)
X-ray fluorescence analysis with an evaluation of the Kalpha/Kbeta or Lalpha/Lbeta count rate ratios enables a layered structure to be recognized, because the measured ratio of two lines of one element depends on the depth distribution of this element in the analyzed objects. Several specimens consisting of layers of various pigments were analyzed to demonstrate the possibilities of the proposed technique. Then the Lalpha/Lbeta technique was applied in an investigation of cinnabar distribution in mediaeval manuscripts.
Keywords: sloučeniny rtuti; History, Medieval; Coloring Agents; X-Ray Diffraction; Manuscripts as Topic; difrakce rentgenového záření; Mercury Compounds; barvicí látky; dějiny středověku; rukopisy jako téma